LSDBs and How They Have Evolved. Issue 6 (14th March 2016) - Dalgleish, Raymond
ABSTRACT: Locus specific databases (LSDBs) make a key contribution to our understanding of heritable and acquired human disorders, disease susceptibility, and adverse drug reactions. As data have accumulated in LSDBs, a greater reliance on their use has arisen in clinical practice. Even though LSDBs have existed in recognizable form for only a quarter of a century, their origin lies in the manual cataloging of data that began around 50 years ago. Analysis and recording of sequence variation in the globin genes, and the proteins which they encode, can confidently be said to be the foundation for what we now refer to as LSDBs. Their growth over the years has primarily been underpinned by software developments and the advent of the World Wide Web. However, it is also important to recognize the evolution of reporting standards and reference sequences, without which accurate and consistent reporting of sequence variants would be impossible. Nowadays, LSDBs exist for many human protein‐coding genes and the focus of efforts has moved toward minor tidying up of the variant reporting nomenclature and processes for assuring the completeness, correctness, and consistency of the data. The next 25 years will doubtless witness further developments in the evolution of LSDBs.